Highway 61 revisited : the tangled roots of American jazz, blues, & country music - Santoro, Gene (Oxford University Press, 2004)
What do Louis Armstrong, Ray Charles, Bob Dylan, Willie Nelson, Tom Waits, Cassandra Wilson, and Ani DiFranco have in common? In Highway 61 Revisited, acclaimed music critic Gene Santoro says the answer is jazz-not just the musical style, but jazz's distinctive ambiance and attitudes. As legendary bebop rebel Charlie Parker once put it, "If you don't live it, it won't come out of your horn." Unwinding that Zen-like statement, Santoro traces how jazz's existential art has infused outstanding musicians in nearly every wing of American popular music-blues, folk, gospel, psychedelic rock, country